Nursing management of pressure injuries in a diabetic patient with transverse injury of the spinal cord (1例脊髓横贯性损伤合并糖尿病患者压力性损伤的护理) - HOU Pengxiao (候朋晓); ZHANG Fengyao (张凤尧); SUN Lei (孙磊); HAN Jianping (韩建萍) (中西医结合护理)
This paper summarized the nursing measures of pressure injuries in a diabetic patient with transverse injury of the spinal cord. Based on the multi-disciplinary consultation, a set of nursing interventions such as strengthening health education and improving treatment compliance were carried out. Individualized dressing change plan was developed with the help of experts in ostomy and wound care, in order to improve the wound healing, relieve pain and improve the quality of life among patients. (本文总结1例脊髓横贯性损伤合并糖尿病患者压力性损伤的护理措施。通过对患者多学科会诊, 加强健康教育, 提高依从性, 聘请伤口造口专业学组专家指导, 为患者伤口制定个性化的换药方案, 达到促进伤口愈合、减轻患者痛苦、提高生活质量的目的。)